Developing a creative pedagogy to understand the university experience of non-traditional students - Gosling, Helena; Burke, Lol; MacLennan, Sarah (PRISM: Casting New Light on Learning, Theory and Practice, 2020)
Despite the presence of a widening participation agenda, people with criminal convictions face a number of barriers accessing and participating in higher education (Office for Students, 2019). This may be due to unspent criminal convictions (Unlock, 2018), limited confidence and self-esteem (Champion and Noble, 2016), a lack of previous educational attainment (Prison Reform Trust, 2017) and/or presence of risk-adverse, bureaucratic, university admission processes (Bhattacharya et al., 2013). As a result, people with criminal convictions are not only under-represented throughout the sector (Unlock, 2018) but completely overlooked when it comes to understanding their university experience. To address this longstanding issue, the authors have developed an educational opportunity (utilising the Learning Together programme) for criminal justice academics, students, practitioners and service users to come together and learn from one another through lived experience, professional practice and Creative Pedagogy. Learning Together was originally developed and implemented by Dr Amy Ludlow and Dr Ruth Armstrong at the University of Cambridge to provide opportunities for university students to learn alongside people serving a custodial sentence (Armstrong and Ludlow, 2016).